An Efficient Boron Source Activation Strategy for the Low-Temperature Synthesis of Boron Nitride Nanotubes - Wang, Ying; Zhang, Kai; Ding, Liping; Wu, Liyun; E, Songfeng; He, Qian; Wang, Nanyang; Zuo, Hui; Zhou, Zhengyang; Ding, Feng; Hu, Yue; Zhang, Jin; et al. (Nano-Micro Letters, 2024)
Lowering the synthesis temperature of boron nitride nanotubes (BNNTs) is crucial for their development. The primary reason for adopting a high temperature is to enable the effective activation of high-melting-point solid boron. In this study, we developed a novel approach for efficiently activating boron by introducing alkali metal compounds into the conventional MgO–B system. This approach can be adopted to form various low-melting-point AM–Mg–B–O growth systems. These growth systems have improved catalytic capability and reactivity even under low-temperature conditions, facilitating the synthesis of BNNTs at temperatures as low as 850 °C. In addition, molecular dynamics simulations based on density functional theory theoretically demonstrate that the systems maintain a liquid state at low temperatures and interact with N atoms to form BN chains. These findings offer novel insights into the design of boron activation and are expected to facilitate research on the low-temperature synthesis of BNNTs. Highlights: 1 Developed more efficient boron activation strategies, while establishing various low-melting growth systems. 2 The preparation temperature of boron nitride nanotubes has been reduced to 850 °C.